The structural relationships among Korean golf instructors’ human service quality, customer emotional response, customer satisfaction, and customer learning transfer - Kwon, Ki Hong; Kim, Yong-Ki (Frontiers in Psychology, 2025)
This study investigates the structural relationships among golf instructors’ human service quality, customers’ emotional responses, customer satisfaction, and learning transfer in the context of golf lesson participants in South Korea. The research focuses on adult golfers who received instruction within the past 2 years at outdoor golf practice ranges. Data were collected from 376 valid responses using a structured questionnaire and analyzed using structural equation modeling (SEM). The results reveal that the human service quality of golf instructors has a significant positive effect on customers’ positive emotional responses and a significant negative effect on their negative emotional responses. Furthermore, both the instructors’ service quality and customers’ positive emotional responses significantly contribute to higher customer satisfaction. Conversely, negative emotional responses were found to decrease satisfaction. Regarding learning transfer, customer satisfaction positively influences the extent to which golf lesson content is effectively applied, while negative emotional responses negatively affect this process. Mediation analysis further indicates that the impact of human service quality on learning transfer is significantly mediated by both customer satisfaction and emotional responses. In particular, positive emotional responses enhance learning transfer through increased satisfaction, suggesting a dual pathway of influence. These findings underscore the importance of emotional experience and perceived service quality in sports instruction settings. Golf instructors should prioritize strategies that foster positive emotional experiences and satisfaction to optimize learning outcomes and promote the transfer of skills from training to actual performance.